Evaluation of wound healing activity of ethanolic extract of Azadirachta Indica leaves on incision and excision wound models in Wister albino rats - Nagesh, H. N.; Basavanna, P. L.; Kishore, M. S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Wound healing is complex cellular and biochemical cascade that lead to restitution of integrity and function. Recently, the traditional use of plants for wound healing has received attention by the scientific community, as traditional medicine is a source of less expensive, comprehensive medical care, especially in developing countries. Azadirachta indica (Neem) is well-known in India, as one of the most versatile medicinal plants having a wide spectrum of biological activity. Hence, this study was undertaken to evaluate the wound healing activity of the ethanolic extract of A. indica leaf in the experimentally-induced wound in rats. Methods: The healing effect produced by A. indica extract was assessed by the rate of wound contraction histopathology and skin breaking strength by using excision wound model and incision wound model in Wister albino rats. This was compared with control (soft white paraffin) and standard (1% w/w framycetin sulfate ointment). The results have been analyzed by calculating the mean values, standard deviation and compared by using student t-test. Results: The ethanol extract of leaves of A. indica significantly promoted the wound healing activity in both excision and incision wound models. Conclusion: The study revealed promising wound healing activity of ethanolic extract of A. indica and provides a scientific rationale for the traditional use in the management of wounds.